2007
DOI: 10.1177/1049732307307918
|View full text |Cite
|
Sign up to set email alerts
|

First Nations People's Challenge in Managing Coronary Artery Disease Risk

Abstract: First Nations peoples bring a particular history and cultural perspective to healing and well-being that significantly influences their health behaviors. The authors used grounded theory methods to describe and explain how ethnocultural affiliation and gender influence the process that 22 First Nations people underwent when making lifestyle changes related to their coronary artery disease (CAD) risk. The transcribed interviews revealed a core variable, meeting the challenge. Meeting the challenge of CAD risk m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…Consistent with the findings of King, Sanguins, McGregor, and LeBlanc () and Clark et al. (), this study found that people of low SES faced a considerable amount of difficulty with regard to meeting their basic needs, such as paying rent and bills, and fulfilling the demands of all members of the household within a scarce income, and this competed with purchasing high‐quality food.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with the findings of King, Sanguins, McGregor, and LeBlanc () and Clark et al. (), this study found that people of low SES faced a considerable amount of difficulty with regard to meeting their basic needs, such as paying rent and bills, and fulfilling the demands of all members of the household within a scarce income, and this competed with purchasing high‐quality food.…”
Section: Discussionsupporting
confidence: 88%
“…This has been found in countries such as America (Ma, 1999; Pang et al, 2003), Canada (King et al, 2007), and Australia (Hsu-Hage et al, 2001; Kwok & Sullivan, 2007). In the main, these studies have reported the end stage or the results of self-management among Chinese people and recorded that they underutilized health care services.…”
Section: Discussionmentioning
confidence: 88%
“…A delay in help seeking can bring fatal consequences and is a major problem for both patients and health care providers (WHO, 2010). The rates of chronic diseases, such as cardiovascular diseases, are much higher in the older population who attend late at services because they accept symptoms and present only when a new emergency or health care problem occurs, if they attend at all (Goldberg et al, 1998; Howse, Ebrahim, & Gooberman-Hill, 2005; King, Sanguins, Mcgregor, & Leblanc, 2007; Tod, Read, Lacey, & Abbott, 2001). Additionally for minority groups, cultural and ethnic issues relating to place and health care systems also play an important part in delayed help seeking (Marmot, 2010; Scheppers, Dongen, Dekker, Geertzen, & Dekker, 2006).…”
mentioning
confidence: 99%
“…"I think I've mentioned that, the native women, they're very quiet, they're not as talkative and they [the physicians] ask them questions and sometimes it's just... you know, quiet…" (King et al, 2007) The level of patient participation in health information interactions can be explained by individual personality factors, the level of trust in the health professional and cultural factors. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59…”
Section: Patient Participation In Educational Interactionsmentioning
confidence: 99%
“…Nobody even told me I'd had a heart attack." (Webster et al, 2002) Some participants felt that the nurse or pharmacist was a good source of information and had the time available to explain information in a lay language (Astin et al, 2008;Cartledge et al, 2018;Hagberth et al, 2008;King et al, 2007;King et al, 2006;Kristofferzon et al, 2007;Svavarsdottir et al, 2016;Wright et al, 2001;Yamada & Holmes, 1998), whereas other participants preferred information to be provided by a doctor (Abramsohn et al, 2013;Astin et al, 2008;Hagberth et al, 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w 11 2008; King et al, 2007;Pryor, Page, Patsamanis, & Jolly, 2014;…”
Section: Finding a Common Languagementioning
confidence: 99%